Al Quran Se Jimat Sebagai Ensiklopedia Sejarah Lahirnya Pulau Gili Iyang - Azisi, Azisi; Badri, Badri; Luthfi, Moh. Hasan; al Farisi, Muhammad (An-Nuqthah, 2024)
Gili Iyang Island, located on the eastern side of Madura Island, possesses a unique tradition of preserving Quranic manuscripts known as Alquran se Jimat. These manuscripts serve not only as religious texts but also as symbols of the local community's cultural identity. This study employed a qualitative approach using Participatory Action Research (PAR) methodology. Data were collected through interviews, field observations, and document analysis to understand the historical context, the values contained within the manuscripts, and their practical usage in the daily lives of the community. The findings indicate that the Alquran se Jimat manuscripts hold significant historical value, reflecting the oral traditions and religious practices of the Gili Iyang community. Furthermore, these manuscripts play a crucial role in strengthening social cohesion and cultural identity, as well as positively impacting education and morality within the community. This research highlights the importance of preserving Quranic manuscripts as part of cultural heritage. Recommendations for preservation programs and the development of scholarly values are proposed to ensure the sustainability of this tradition in the future